A Concise Introduction to Elastic Solids An Overview of the Mechanics of Elastic Materials and Structures - Herakovich, Carl T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides an introduction to fundamental concepts of solid mechanics for the uninitiated. It also includes a concise review of fundamentals for those who have been away from the field for a time or are studying for a final exam or engineering license exam. The coverage ranges from fundamental definitions through constitutive equations, axial loading, torsion, bending, thermal effects, stability, pressure vessels, plates and shells, computational mechanics, and fibrous composite materials.
Mechanics of Solids -- Stress -- Strain -- Constitutive Equations -- Equilibrium -- Axial Loading -- Torsion of Cylindrical Bars -- Beam Bending -- Beam Subjected to Transverse Loading -- Beam Deflections -- Thermal Effects -- Stability -- Thin-walled Pressure Vessels -- Plates and Shells -- Computational Mechanics -- Fibrous Composite Materials -- Appendix.
Keywords: Mechanics, Applied; Civil engineering; Materials -- Analysis; Condensed matter; Engineering Mechanics; Civil Engineering; Characterization and Analytical Technique; Condensed Matter Physics